Effective Educational Strategies to Promote Life-Long Musical Investment: Perceptions of Educators - Krause, Amanda E.; Davidson, Jane W. (Frontiers in Psychology, 2018)
While research has broadly considered the wide-ranging intellectual, social, personal and physical benefits of active musical participation across the lifespan, there is little research that explores how music educators work to promote participant investment inside school and beyond. The present research, therefore, aimed to investigate the practices employed by leading music educators within a range of cultural and pedagogical contexts that facilitate investment towards life-long engagement in music. Interviews with North American, European and Australian music educators with both practitioner and research expertise from within school as well as higher education institutions were undertaken to gather reflections on participants’ own practices and beliefs. Content analysis of the interview transcripts revealed deep knowledge and skills relating to teaching music, education philosophy and pedagogy and strong recognition of the support of peers, supervisors, institution/school and local community. It was clear that interviewees were deeply influenced by local, national, and cultural trends. Further, the advice they offered for new/beginning music educators was to think beyond the structure of their own music education and to explore culturally diverse educational experiences for students. Educational approaches that fostered co-production were favored, thus guiding students in their pursuits in learner-directed environments. While the beliefs and practices described are not ‘new’—echoing well-established educational philosophies— all interviewees argue for a shift from the prevailing pedagogical practice based on expertise training to the promotion cultural connectedness and sharing in and through musical experience. These findings are discussed in terms of Self-Determination Theory, to provide a framework for how music educators can facilitate long-term musical investment through the development of autonomous engagement to generate personal meaning and value in music, which can translate to deeper, longer musical investment. Exploring these pedagogical practices and beliefs in terms of Self-Determination Theory is a significant addition to the literature, enabling the consideration of the type of motivation required to stimulate and develop long-term interest in music.